Existence of Solution for Double-Phase Problem with Singular Weights - Zhi-Yuan Chen; Bin Ge; Wen-Shuo Yuan; Xiao-Feng Cao (Advances in Mathematical Physics)
The aim of this paper is to establish the existence of solutions for singular double-phase problems depending on one parameter. This work improves and complements the existing ones in the literature. There seems to be no results on the existence of solutions for singular double-phase problems.